Center specificity in the limited sampling model (LSM): can the LSM developed from healthy subjects be extended to disease states? - Mahmood, I (International journal of clinical pharmacology and therapeutics, 2003)
Area under the curve (AUC) can be related to the therapeutic or toxic effect of a drug. In order to accurately measure AUC, multiple blood samples are required, but in a clinical setting, frequent blood sampling from the patients is time-consuming and expensive. The limited sampling model (LSM) is one of the approaches that is gaining popularity due to its simplicity for the estimation of AUC using 1 - 3 samples. Despite its simplicity, the LSM has some shortcomings. One of the major drawbacks of the LSM is that the LSM developed under a given condition may not be extended to other conditions. For example, the LSM developed from healthy subjects may not be extended to disease states such as renal or hepatic impairment or vice versa. This characteristic of the LSM can be referred to as "center-specific". In this investigation, the LSM developed from the healthy subjects was used to predict AUC in patients with renal or hepatic impairment. Two sets of simulated plasma concentration versus time data for 2 antihypertensive drugs and measured plasma concentration versus time data for 2 representative drugs (A and B) were used in the analysis. The results of the study indicate that the LSM developed from healthy subjects is inadequate to predict AUC in patients with hepatic or renal impairment, indicating center specificity of the LSM.